2019
DOI: 10.18502/acta.v57i1.1753
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of a Clinically Silent Nephrolithiasis in Baghdad Population: An Initial Ultrasound Screening Study From Iraq

Abstract: Abstract- Asymptomatic or clinically silent kidney stones are possibly serious because, in their expected passage, they may cause infection, obstruction and renal impairment. The purpose of this study was to determine the prevalence of silent kidney stones in a sample of Baghdad population and consider how this value could affect the justification for a screening system. To our best knowledge, this is the first study of its kind conducted in Iraq. We investigated 714 consecutive patients who sustained an abdom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
0
0
Order By: Relevance
“…18 However, the average age in our study was less than that observed in Karachi was 44 years, Kuwait was 41.91 years and Thailand was 40.3 years. 19,20 Most common presenting complaint was left flank pain followed by bilateral Similar pattern was observed in studies done in Kuwait, the USA, and Karachi. 20 Modification in urinary PH additionally plays an imperative part in the combination of kidney calculus, on the grounds that in specific calculi, PH is.…”
Section: Discussionsupporting
confidence: 73%
“…18 However, the average age in our study was less than that observed in Karachi was 44 years, Kuwait was 41.91 years and Thailand was 40.3 years. 19,20 Most common presenting complaint was left flank pain followed by bilateral Similar pattern was observed in studies done in Kuwait, the USA, and Karachi. 20 Modification in urinary PH additionally plays an imperative part in the combination of kidney calculus, on the grounds that in specific calculi, PH is.…”
Section: Discussionsupporting
confidence: 73%
“…The researcher compared ESWL to semirigid URS for proximal ureteral stones. Extracorporeal shock wave lithotripsy (ESWL) is widely used to treat 10-mm proximal ureteral stones due to its low complication rate and noninvasiveness [3] . ESWL retreats more often and takes longer to eliminate stones.…”
Section: Introductionmentioning
confidence: 99%